DHEA and cognitive function in the elderly. Issue 145 (January 2015) - Maggio, Marcello; De Vita, Francesca; Fisichella, Alberto; Colizzi, Elena; Provenzano, Sandra; Lauretani, Fulvio; Luci, Michele; Ceresini, Graziano; Dall'Aglio, Elisabetta; Caffarra, Paolo; Valenti, Giorgio; Ceda, Gian Paolo
Highlights: DHEA and DHEAS are classified as neurosteroids. In vitro and animal studies show a role for DHEA/S in cognitive function. Cross-Sectional positive association between DHEA/S and cognitive domains. DHEA/S is not a strong independent predictor of cognitive impairment. RCTs do not support DHEA treatment for improving cognition in adult-older subjects. Abstract: The adrenal prohormone dehydroepiandrosterone (DHEA) and its sulphate conjugate (DHEAS) steadily decrease with age by 10% per decade reaching a nadir after the age of 80. Both DHEA and DHEAS (DHEA/S) exert many biological activities in different tissues and organs. In particular, DHEA and DHEAS are produced de novo in the brain, hence their classification as neurosteroids. In humans, the brain-to-plasma ratios for DHEA and DHEAS are 4–6.5 and 8.5, respectively, indicating a specific neuroendocrine role for these hormones. DHEA/S stimulates neurite growth, neurogenesis and neuronal survival, apoptosis, catecholamine synthesis and secretion. Together with antioxidant, anti-inflammatory and anti-glucocorticoid properties, it has been hypothesized a neuroprotective effect for DHEA/S. We conducted an accurate research of the literature using PubMed. In the period of time between 1994 and 2013, we selected the observational human studies testing the relationship between DHEA/S and cognitive function in both sexes. The studies are presented according to the cross-sectional and longitudinal design and to the positive or neutral effects on different domains of cognitive function. We also analysed the Clinical Trials, available in the literature, having cognitive domains as the main or secondary outcome. Although the cross-sectional evidence of a positive association between DHEA/S and cognitive function, longitudinal studies and RCTs using DHEA oral treatment (50 mg/day) in normal or demented adult–older subjects, have produced conflicting and inconsistent results. In summary, the current data do not provide clear evidence for the usefulness of DHEA treatment to improve cognitive function in adult–older subjects. This article is part of a Special Issue entitled 'Essential role of DHEA'.